Sociodemographic and clinical features of men and women with eating disorders: a diagnosis-matched, retrospective comparison among inpatients - Traut, Philipp; Halbeisen, Georg; Braks, Karsten; Huber, Thomas J.; Paslakis, Georgios (Frontiers in Psychiatry, 2023)
Introduction Eating disorders (EDs) are among the most severe mental disorders in women and men, often associated with high symptom burden and significant limitations in daily functioning, frequent comorbidities, chronic course of illness, and even high mortality rates. At the same time, differences between men and women with EDs remain poorly explored. Methods In this study, we compared 104 men to 104 diagnosis-matched women with EDs regarding sociodemographic and clinical features. Using latent class mixture modelling, we identified four distinct patient subgroups based on their sociodemographic features. Results Men with EDs had significantly higher odds than women to belong to a “single-childfree-working” class. Moreover, while there were few overall differences in ED-related symptoms and general psychopathology between men and women, single-childfree-working men with EDs presented with higher general psychopathology symptoms than men in the other classes. Discussion We discuss how considering sex and gender along with further sociodemographic differences in EDs may help to improve ED diagnosis and treatment.